1980
DOI: 10.1002/bit.260220506
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bulking and physicochemical–biological properties of activated sludges

Abstract: SummaryResearch into bulking in laboratory-scale activated-sludge plants are reported upon. A correlation between sludge volume index (SVI) and hiopolymrr content (exocellular polymer, ECP) has been determined for sludge obtained under various operating conditions and with different chemical and physical characteristics. This paper interprets that correlation. A method for ECP determination that is quicker and just as precise as the gravimetric one and which enables this parameter to be used not only to interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…The reported influencing factors include floe size, 4 DO and/or organic loadings, M1 -7381 nitrogen and phosphorus content, 82 -83 elevated metal concentrations, 84 mixed liquor SS, 85 treatments prior to aeration, 86 " 89 deficiency of micronutrient concentrations, 90 -91 mixed liquor turbulence, 4692 different types of carbonaceous sources, 87 -93 " 95 exocellular polymers, 96 substrate feeding patterns, 97101 substrate accumulation capacity of microorganisms or substrates oxidized, 93 -102 aeration basin configurations, 89 -103 pH, septic wastes, temperature, 1 etc. Detailed reviews on these influencing factors are available in the literature.…”
Section: Crc Critical Reviews In Environmental Controlmentioning
confidence: 99%
“…The reported influencing factors include floe size, 4 DO and/or organic loadings, M1 -7381 nitrogen and phosphorus content, 82 -83 elevated metal concentrations, 84 mixed liquor SS, 85 treatments prior to aeration, 86 " 89 deficiency of micronutrient concentrations, 90 -91 mixed liquor turbulence, 4692 different types of carbonaceous sources, 87 -93 " 95 exocellular polymers, 96 substrate feeding patterns, 97101 substrate accumulation capacity of microorganisms or substrates oxidized, 93 -102 aeration basin configurations, 89 -103 pH, septic wastes, temperature, 1 etc. Detailed reviews on these influencing factors are available in the literature.…”
Section: Crc Critical Reviews In Environmental Controlmentioning
confidence: 99%
“…The EPS quantity and quality (Table 1) gave additional information about the sedimentation behavior of the sludge. Beccari et al (1980) reported a correlation between EPS quantity and sludge settleability. A very low EPS content causes a reduction in flocculation due to the lack of polymer material.…”
Section: Resultsmentioning
confidence: 99%
“…2,3) or to modify the surfaces in a specific and pre-determined way and then to examine the effect that this has on the sludge itself (eg. 4,5).…”
Section: Introductionmentioning
confidence: 99%